TRADISI MEGOAK-GOAKAN DI KABUPATEN BULELENG DAN RELEVANSINYA TERHADAP PARIWISATA BUDAYA DI BALI (KAJIAN ETNOPEDAGOGI) - Ardiawan I Ketut Ngurah (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2017)
In essence, Megoak-goakan is an ancestral cultural heritage tradition which is done and preserved. Megoak-goakan is an original traditional  game from North Bali precisely in Panji Village, Sukasada Distric, Buleleng Regency. Megoak-goakan itself is a restaging of a heroic history of Ki Barak Panji Sakti known as the Hero of Buleleng Bali when conquering Blambangan  Kingdom in  East  Java.  The  attractiveness  of local  values in Megoak-goakan tradition, besides being able to inspires the growth of local indigenous norm, on the other side it becomes the value of life that gives significance to the life and their interactions. These are seen from the agile movements demonstrated by the players, who sometimes running, dancing, squatting, creeping around, turning around, or jumping around. Beside the interaction activities in Megoak-goakan are also seen from the procession of gamelan song and even the costume used resembles the warrior of society in the context of a kingdom. The strategic values of local culture  have  inspired  various  regions  to  develop  local  potential  in tourism  development. Furthermore, in the context of ethnopedagogical study, that is as an educational practice based on local indigenous in various domains and emphasizing knowledge or local indigenous as a source of innovation and skills that can be empowered for the welfare of society where local indigenous is concerned with how knowledge is generated, saved, applied, managed and inherited. Megoak-goakan has the values of local indigenous that include philosophical, anthropological, sociological, and psychological values which are interesting to be elaborated more.Keywords: Ethnopedagogy, Megoak-goakan, Tourism